Metabolomics and a breath sensor identify acetone as a biomarker for heart failure. (25th November 2020) - Gladding, P.A; Young, R; Cooper, M; Holland, U; Loader, S; Chapman, L; Chapman, A; Smith, K; Zarate, E; Villas-Boas, S; Green, S; Thorstensen, E; et al.
Abstract: Introduction: Metabolomics delivers more biological and clinical insight than targeted investigations. We applied metabolomics to patients with heart failure (HF) with reduced ejection fraction (HFrEF). Methods: 46 patients with HFrEF and 20 controls underwent metabolomic profiling, including liquid/gas chromatography mass spectrometry (LC-MS/GC-MS), nuclear magnetic resonance (NMR) metabolomics and solid-phase microextraction (SPME) volatilomics in plasma and urine. HFrEF was defined using left ventricular global longitudal strain (GLS) <18%, ejection fraction <50% and NTproBNP ≥35 pmol/L. A low cost consumer breath acetone (BrACE) sensor validated SPME results in 69 patients. Results: 34 metabolites were identified by GCMS, 33 by LCMS and 2 volatiles by SPME (acetone, 2-pentanone in plasma and urine). Alanine, aspartate and glutamate, citric acid cycle, arginine biosynthesis, glyoxylate and dicarboxylate metabolism were altered in HFrEF. Plasma acetone correlated with NT-proBNP (r=0.59, 95% CI 0.4 to 0.7), triacylglycerol (55:9), 2-oxovaleric and cis-aconitic acid, involved with ketone metabolism and mitochondrial energetics. BrACE >1.5 ppm discriminated HF from other cardiac pathology (AUC 0.88, 95% CI 0.77 to 0.99, P<0.0001). Conclusion: Breath acetone was detectable in HFrEF patients using a consumer sensor ($1/test) and although not cardiac specific, discriminated HF from other cardiac pathology. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Health Research Council of New Zealand